Gaming Perspectives: Insights Into Disco Elysium as a Tool for EFL Learning - Revi Nauval Ilhansyah (Proceeding of the International Conference on Global Education and Learning, 2024)
The integration of video games into education has garnered attention for its potential to enhance learning experiences, particularly in fostering engagement and autonomous skill development. This qualitative study investigates EFL (English as a Foreign Language) learners' perceptions of using Disco Elysium, a narrative-driven role-playing game, as a supplementary tool for language learning. Data were collected through semi-structured interviews and thematic analysis, focusing on the experiences of EFL learners who engaged with the game's complex linguistic and narrative content. The findings reveal that participants perceive Disco Elysium as a unique and immersive learning medium, aiding in vocabulary acquisition, reading comprehension, and critical thinking. However, challenges such as the game's advanced vocabulary, cultural references, and morally complex themes were also identified. By centering on learner perspectives, this study contributes to the limited research on the role of narrative-driven games in language learning. The results provide insights into how such games can be integrated into educational contexts to complement traditional EFL learning methods.